2022
DOI: 10.1055/s-0041-1738425
|View full text |Cite
|
Sign up to set email alerts
|

Additive-Free Synthesis of 3H-1,2,4-Triazol-3-ones via a Formal [3+2] Cycloaddition Reaction of Hydrazonoyl Chlorides with KOCN

Abstract: A direct and speedy approach for the synthesis of 1,5-disubstitued-3H-1,2,4-triazol-3-ones via a formal [3+2] cycloaddition reaction of hydrazonoyl chlorides with KOCN is described. The reaction proceeds in EtOH at room temperature with no need for any base and catalyst. KCl is the sole byproduct of this efficient synthetic procedure which can be isolated after reaction completion using water in which the products precipitated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…[36][37][38] The drawback of alternative synthetic approaches for the synthesis of 1,2,4-triazole-3-ones made us to envisage an innovative mild electrochemical pathway to reach our targeted products. In line with our ongoing interest regarding new green procedures for the synthesis of 1,2,4-triazole-3-ones scaffold, [39] herein, we disclose the first electrochemical method for the synthesis of 1,2,4-triazole-3-ones through direct C(sp 2 )-H abstraction of hydrazones under environmentally benign conditions. In this electrochemical C(sp 2 )-H abstraction route, catalytic amount of iodide salt directly produced hydrazonoyl halides for the next step of the reaction without utilizing expensive electrolytes, eccentric reagents, and metal catalysts.…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…[36][37][38] The drawback of alternative synthetic approaches for the synthesis of 1,2,4-triazole-3-ones made us to envisage an innovative mild electrochemical pathway to reach our targeted products. In line with our ongoing interest regarding new green procedures for the synthesis of 1,2,4-triazole-3-ones scaffold, [39] herein, we disclose the first electrochemical method for the synthesis of 1,2,4-triazole-3-ones through direct C(sp 2 )-H abstraction of hydrazones under environmentally benign conditions. In this electrochemical C(sp 2 )-H abstraction route, catalytic amount of iodide salt directly produced hydrazonoyl halides for the next step of the reaction without utilizing expensive electrolytes, eccentric reagents, and metal catalysts.…”
Section: Introductionmentioning
confidence: 61%
“…Finally, aryl sulfonyl hydrazones 1 q – 1 t afforded the corresponding five‐membered rings 3 q – 3 t in 71–80 % yields. Also, it should be considered, although in our recently published article, [39] the yield of similar products were generally upper in 20 to 40 %, but the cost efficiency in this electrochemical approach is more valuable for the preparation of products 2 . In fact in this manner, the starting material for the formation of 1,2,4‐triazol‐3‐ones, changed from multistep synthesized hydrazonoyl halides to easily attainable hydrazones.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The same heterocycles are formed by the interaction of hydrazones 19 and potassium cyanate in the presence of molecular iodine and tertbutyl hydroperoxide (Scheme 7). [37] If we pay attention to the conditions of the last reaction, we can find an analogy with the method given below (in scheme 65) for the preparation of triazoles from hydrazones, [38] which also uses TBHP and molecular iodine. But the authors [38] of this earlier work do not propose the formation of the intermediate hydrazonoyl iodide.…”
Section: Methods For Preparing Hydrazonoyl Halidesmentioning
confidence: 99%
“…The molecular iodine-catalyzed reaction of hydrazones 216 with aliphatic amines 217 in the presence of TBHP results in the formation of 1,3,5-trisubstituted 1,2,4-triazoles 218 (Scheme 66). A more recent study [37] suggested the formation of hydrazonoyl iodide in a similar reaction using TBHP and an iodinereleasing moiety. In the case cited below [38] approx- imately the same initial transformations occur.…”
Section: Syntheses Of Triazoles From Hydrazonoyl Halidesmentioning
confidence: 99%